Distribution, Diversity, and Ecological Risks of Microplastics in Mangrove Ecosystems of a Southeastern Chinese Estuary - Fengrun Wu; Chengyi Zhang; Xueyan Li; Sha Liu; Jinpu Wang; Weiqi Huang (Toxics, 2025)
Mangrove ecosystems, serving as critical barriers at land–sea interfaces, face increasing threats from microplastic pollution. This study investigates the spatial distribution, diversity, and ecological risks of microplastics in sediments from the Zhangjiang Estuary mangroves, in southeastern China. Sampling was conducted along two gradients: upstream–downstream and interior–edge habitats. The results revealed an average microplastic abundance of 219.5 ± 21.7 items·kg−1, dominated by fragments (53.3%) and fibers (35.0%). Additionally, 27.8% of the particles were in the 63–200 μm range, while 38.3% fell within the 200–500 μm range. A longitudinal decline in abundance from upstream to downstream was observed. Meanwhile, interior habitats exhibited significantly higher microplastic accumulation (292.86 ± 31.49 items·kg−1) than edge zones (142.50 ± 17.87 items·kg−1) (p < 0.05). The diversity index decreased downstream, with higher diversity in interior habitats, likely due to reduced terrestrial microplastic inputs and stronger tidal sorting in those areas. The ecological risk assessments indicated lower risks in Zhangjiang mangroves compared to global counterparts, though risks were elevated in interior habitats due to higher abundances of hazardous polymers (PVC, PS, PE). This study highlights the role of mangroves as microplastic sinks and advocates for multidimensional risk assessments integrating physical characteristics to guide conservation strategies in vulnerable estuarine ecosystems.